3D printing filament recycling for a more sustainable library makerspace. Issue 2 (10th November 2021) - Bossart, Jean L.; Gonzalez, Sara Russell; Greenberg, Zachary
Abstract: 3D printing services are an increasingly popular offering in many academic library makerspaces. However, failed prints, and simply the printing process itself, can generate substantial waste. Through a grant from a regional library consortium, the feasibility of recycling waste 3D plastic and reconstituting it into new 3D printing filament was explored and tested. Other 3D printing makerspaces on campus have asked about recycling waste filament or providing that material to the library to recycle. This paper will discuss the methodology, benefits, and challenges of recycling 3D printing filament in an effort to make 3D printing more sustainable.